2004
DOI: 10.1128/jvi.78.18.9837-9841.2004
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Analyses of Vesicular Stomatitis Strains with Rearranged Genomes Reveal Replicative Disadvantages

Abstract: Gene expression of the nonsegmented negative-strand RNA viruses is determined by the position of each gene relative to that the single 3 promoter. The general order of genes among all of the viruses of the order Mononegavirales is highly conserved. In previous work we generated recombinant viruses in which the order of the three central genes of the prototypical rhabdovirus, vesicular stomatitis virus, was rearranged to all six possible permutations. While some of these viruses replicated less well than the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 25 publications
4
35
0
Order By: Relevance
“…1). As previously established, however, differences in fitness (or growth) can be demonstrated by alternative assays, such as coinfection assays, that may identify subtle effects of genetic changes on replication kinetics (33)(34)(35). Furthermore, these data are not entirely surprising because (i) both clades were individually successful in nature in infecting mosquitoes and in causing illness in humans (6), and (ii) in vitro infections can fail to accurately represent the complexity of natural transmission cycles.…”
Section: Growth Of Clades Ni-1 and Ni-2b In Aag2 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). As previously established, however, differences in fitness (or growth) can be demonstrated by alternative assays, such as coinfection assays, that may identify subtle effects of genetic changes on replication kinetics (33)(34)(35). Furthermore, these data are not entirely surprising because (i) both clades were individually successful in nature in infecting mosquitoes and in causing illness in humans (6), and (ii) in vitro infections can fail to accurately represent the complexity of natural transmission cycles.…”
Section: Growth Of Clades Ni-1 and Ni-2b In Aag2 Cellsmentioning
confidence: 99%
“…Another strategy to apply selective pressure to viruses in culture is by coinfection; this serves as a means to detect a replicative advantage between closely related viruses (6,(33)(34)(35). In the competition experiments presented here, the relative amounts of each clade are reported using a replicative index, defined as ln[(NI-2B/ NI-1 ratio on day x)/(NI-2B/NI-1 ratio on day 0)] (34, 37).…”
Section: Growth Of Clades Ni-1 and Ni-2b In Aag2 Cellsmentioning
confidence: 99%
“…Vesicular stomatitis virus has a rapid life cycle; cytopathic effects (CPEs) are typically evident by 24 hr postinfection as virus-infected cells round up and die by apoptosis (Kopecky et al, 2001). The burst size of a VSV-infected cell ranges between 500 and 6000 viruses per cell (Novella et al, 2004). The virus is sensitive to the antiviral effects of interferon (IFN)-a=b produced by infected cells to limit viral replication and spread to neighboring cells.…”
Section: Introductionmentioning
confidence: 99%
“…This led to a stepwise decrease in N mRNA production and protein expression (Wertz et al 1998). The initial fitness of the VSV variants was low (Novella et al 2004), but fitness gains were observed in evolutionary time, and fitness improved the most for the variant with the lowest initial fitness (Pesko et al 2015). Nevertheless, the variant with the wild-type gene order still grew better than the other variants.…”
mentioning
confidence: 99%
“…For example, different expression levels for viral gene products can arise through the generation of subgenomic RNAs (de Haan et al 2003), frameshifts (Chung et al 2008), stuttering of the RNA polymerase in intergenic regions (Wertz et al 1998), having multiple genome segments with different regulatory elements (Sullivan and Ahlquist 1997), or varying the frequency of different genome segments (Sicard et al 2013). Altering gene order in viral genomes therefore can be associated with great fitness costs (Novella et al 2004;Springman et al 2005), and rearrangement of essential genes is not always reversible (Wertz et al 1998). Nevertheless, it is not always obvious why gene order has been so well conserved in viruses.…”
mentioning
confidence: 99%